The Effect of Flipped Classroom Through LINE in Teaching English Articles - Supiani, munjaroh Dwi; Arifani, Yudhi; Asmana, Candra Hadi (Universitas Muhammadiyah Gresik, 2020)
Teaching in English is a worldwide priority, but teaching methodology is not necessarily in line with the changing needs of students. Therefore, this study explores the effects of flipped classes on material English articles, and compares this instructional design with the traditional instruction. Design of experimental research consisting of group experiments and controls. The experimental group (N = 23) is subject to flipped instruction, where learning content is provided outside of class time through electronic means of LINE and class time is used for activities. In the control group, students (N = 23) are taught in traditional methods, where learning is delivered during classes and additional exercises are given outside class time.The subect of the study was eight grade student of Madrasah Tsanawiyah Asy'ariyah.Pre test and post test are given to students in advance and at the end of material to know the impact of two teaching methods in English articles. Findings show that students in flipped classroom do English articles better in the post-test than in the pre- test.The pre and post test values of the experimental group showed that the significance value (2-tailed) was 0,000 (p <0.05). So the results of the initial test and final test underwent significant changes.The result from the flipped and traditional approaches is very significant. Most students who flipped generally have a good perception of the flipped class. With This research, it is hoped that the teacher can apply this strategy in different material. For student must be more understand about English articles.